THE CONDITIONS FOR COMPENSATION OF MECHANICAL AND MAGNETIC POWER LOSSES WHILE MUTUAL LOADING TRACTION OF ELECTRIC MACHINES ACCORDING TO THE SCHEME OF POTIER - Afanasov, A. M. (Science and Transport Progress, 2009)
The conditions of compensation of magnetic and mechanical losses during the test of hauling electric machines according to the Potier’s chart are considered.